Types, Magnitude and Factors Associated with Medication Administration Errors Among Nurses in Rubanda East Health Sub District. - Atuhaire, Oliva (Kabale University, 2024)
Introduction: Medication administration errors (MAEs) are preventable incidents resulting from the improper use of medication. These errors significantly contribute to poor health outcomes, with an estimated 6,000 to 20,000 patient deaths annually due to MAEs, most of which go unreported. This study aims to assess the types, extent, and factors associated with MAEs among nurses in the Rubanda East Health Subdistrict. Methods: A descriptive cross-sectional study was conducted using a pretested, interviewer-administered questionnaire to collect data from 120 randomly selected nurses in Rubanda East Health Subdistrict. Bivariate logistic regression was used to analyze factors associated with MAEs, and significant variables (p=0.2) were included in a multivariate logistic regression model. Adjusted odds ratios were presented, and data were analyzed using STATA version 14. Results: The study revealed that 54.17% of the nurses committed various types of MAEs. The majority (64.17%) administered underdoses, 54.17% administered overdoses, 50.00% gave the wrong drug, 60.83% administered medication at the wrong time, 43.33% used the wrong route, and 62.50% reported poor documentation. Specifically, 60.83% administered underdoses moderately, 48.33% administered overdoses to a greater extent, and 64.17% administered the wrong drug to a greater extent. MAEs were significantly associated with nurses aged 31-40 years (aOR=2.6; 95%CI=0.849-7.740; p=0.015), female nurses (aOR=2.9; 95%CI=1.049-8.291; p=0.040), poor knowledge of drug administration (aOR=0.4; 95%CI=0.125-1.165; p=0.041), and interruptions during medication administration (aOR=0.4; 95%CI=0.117-1.219; p=0.030). Conclusion: The study found a high prevalence of MAEs among nurses, with common errors including overdoses, overdoses, wrong drug administration, incorrect timing, wrong routes, and poor documentation. Underdoses were commonly administered to a moderate extent, while wrong documentation and wrong drug administration to the correct patient occurred to a greater extent. Factors strongly associated with MAEs included age, gender, poor drug administration knowledge, and interruptions during medication administration.